Leg massage during pregnancy with unrecognized deep vein thrombosis could be life threatening: a case report - Krongkarn Sutham; Sukumpat Na-Nan; Salilthip Paiboonsithiwong; Pakorn Chaksuwat; Theera Tongsong (BMC Pregnancy and Childbirth, 2020)
Abstract Background Traditional massage seems to be safe but not entirely risk free, though serious adverse events are very rare. This report is aimed at illustrating a rare but fatal presentation of massive pulmonary embolism caused by leg massage and also to encourage both massage providers and pregnant women to be aware of undetected or subtle deep vein thrombosis, which could be a life threatening condition as a consequence of leg massage. Case presentation A 25-year-old primigravid Thai woman underwent massage at a traditional massage shop at 25th week of gestation. Shortly after leg and foot massage, she had a sudden onset of dyspnea, followed by consciousness alteration, brief spastic-like convulsion, became unconscious and suffered a cardiac arrest. Basic life support (BLS) at the event scene as well as during transfer and advanced cardiovascular life support (ACLS) at the hospital were provided, resulting in successful resuscitation but persistent coma. Bedside echocardiography showed poor contractility of the dilated right ventricle, and pulmonary embolism was suspected. CT angiography (CTA) revealed multiple concentric intraluminal filling defects within the right and left pulmonary arteries, indicating massive pulmonary embolism. The fetus died in utero and spontaneous labor and vaginal delivery occurred. Conclusion Leg massage in patients with deep vein thrombosis can dislodge thrombi, leading to life threatening pulmonary embolism, and should be contraindicated. Since pregnant women are at a higher risk of undetected or subtle thromboembolism, traditional massage in pregnant women should be contraindicated unless they are proven to have no such risk.